2014
DOI: 10.1038/mt.2013.248
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-elicited Human T Cells Recognizing Conserved Protein Regions Inhibit HIV-1

Abstract: Virus diversity and escape from immune responses are the biggest challenges to the development of an effective vaccine against HIV-1. We hypothesized that T-cell vaccines targeting the most conserved regions of the HIV-1 proteome, which are common to most variants and bear fitness costs when mutated, will generate effectors that efficiently recognize and kill virus-infected cells early enough after transmission to potentially impact on HIV-1 replication and will do so more efficiently than whole protein-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
292
2
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 189 publications
(302 citation statements)
references
References 50 publications
7
292
2
1
Order By: Relevance
“…HIVconsv, which was recently shown to be immunogenic in a phase I clinical trial. 5 We report that IL-10R blockade significantly enhanced both the frequency and function of CD8 C T cell responses to ChAdV63.HIVconsv.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…HIVconsv, which was recently shown to be immunogenic in a phase I clinical trial. 5 We report that IL-10R blockade significantly enhanced both the frequency and function of CD8 C T cell responses to ChAdV63.HIVconsv.…”
Section: Introductionmentioning
confidence: 85%
“…14 ChAdV63.HIVconsv was produced at the Clinical Biomanufacturing Facility (CBF), University of Oxford, UK, as described previously. 5 Experimental animals and immunizations Six-week-old female BALB/c mice were purchased from Harlan. All procedures were conducted in accordance with the UK Animals (Scientific Procedures) Act under Project License PPL 30/2833 and Personal License PIL 40/1027 and approved by the University of Oxford Animal Care and Ethical Review Committee.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Some vaccines tested in Phase I trials have generated T cells that can suppress virus 11 but not yet as well as CD8 T cells from infected patients who control HIV-1 well. Yang et al 10 have shown that this immune parameter, when measured in early infection, is inversely correlated with viral load set point and can predict the rate of CD4 T cell decline; if that result can be confirmed on a larger scale it would be a very useful measure to test potential vaccine effectiveness.…”
mentioning
confidence: 99%